Covid-19 and medical liability: challenges of an unknown disease that became a pandemic - Cárdenas Villarreal, Hugo; Pérez Saavedra, Manuel Antonio (Acta Bioethica, 2020)
The coronavirus health-emergency shows that liability schemes need to discriminate the conceptual instruments available to address a new disease that, additionally, has become a pandemic. This article argues that, regarding new diseases, a fault-based liability schemes prevents health providers from being held liable for consequences that could not have been foreseen or avoided according to the state of knowledge of science. Besides, regarding the public health problem, any liability judgment must take into account changes to the medical lex artis; distinguishing also the eventual liability of health providers from the one that belongs to the authority in charge of the response to the pandemic.